2014
DOI: 10.1039/c4dt01161a
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of Fe3O4 nanoparticles with controlled morphologies using urease and their application in dye adsorption

Abstract: This paper describes a simple and environmentally friendly method for the preparation of highly stable dispersions of Fe3O4 nanoparticles with controlled morphologies, in the same synthesis system for the first time. During the process, the Fe3O4 nanoparticles are formed using urease as a multifunctional reagent, including catalyst, template and dispersant, due to its enzymatic activity and special enzymatic steric structure. A possible formation mechanism for these Fe3O4 nanoparticles, which have various morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…In addition, results of control experiments showed that the presence of Fe 3 O 4 -associated organic substances was required for the generation of rod-like magnetite after the addition of noble metal precursor salts. It has been reported that, in the presence of externally added organic substances, Fe 3 O 4 nanoparticles can self-assemble into nanorods, nanowires or nanosheets without temple through the interplay and balance of dipolar force, electrostatic interaction and van der Waals force 16 41 42 . The self-assembly of Fe 3 O 4 nanoparticles into oriented nanosheets was achieved through using a hydrophilic terpolymer as stabilizer under low pH conditions 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, results of control experiments showed that the presence of Fe 3 O 4 -associated organic substances was required for the generation of rod-like magnetite after the addition of noble metal precursor salts. It has been reported that, in the presence of externally added organic substances, Fe 3 O 4 nanoparticles can self-assemble into nanorods, nanowires or nanosheets without temple through the interplay and balance of dipolar force, electrostatic interaction and van der Waals force 16 41 42 . The self-assembly of Fe 3 O 4 nanoparticles into oriented nanosheets was achieved through using a hydrophilic terpolymer as stabilizer under low pH conditions 42 .…”
Section: Discussionmentioning
confidence: 99%
“…sample S5, related to the electron peaks for Fe 2p in Fe 3 O 4 54,55. No shakeup satellite peaks related to…”
mentioning
confidence: 99%
“…OH − ) has been utilized for regulating the uniform size of TiO 2 nanoparticles [46] and the morphology of Fe 3 O 4 nanomaterials. [47] However, in our case, all the species of OH − , NH 4 + , and CO 3 2− from urea enzymolysis participate in the formation of NH 4 Ga(OH) 2 CO 3 nanotubes. The formation mechanism of NH 4 Ga(OH) 2 CO 3 nanotubes is proposed, and the advantage of Ga 2 O 3 nanotubes over nanoparticles is demonstrated by the enhanced catalytic H 2 evolution from water-splitting.…”
mentioning
confidence: 53%